The indirect effects of direct democracy: Local government size and non-budgetary voter initiatives - Zareh Asatryan (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Recently a wide and empirically-backed consensus has emerged arguing that direct democratic control over government's spending decisions through initiatives and referenda constrains government size. But what happens if budgetary matters are excluded from the voters' right of the initiative? I study this question by extending the analysis to German direct democracy reforms of the mid-1990s, which granted voters wide opportunities to initiate referenda on local issues, but neither the right, nor the responsibility of voting on the implied costs of these initiatives. By exploiting a novel dataset containing detailed information on close to 2,300 voter initiatives in the population of around 13,000 German municipalities from 2002 to 2009, I show that in this sample and in contrast to the Swiss and US evidence direct democracy causes an expansion of local government size by up to 8% in annual per capita expenditure and revenue per observed initiative (on economic projects). The main empirical challenge is the endogeneity of voters' unobserved preferences which simultaneously determine both their propensity towards exploiting their direct democracy rights and their preferences for local public policies. To address this issue I use state- and municipality-varying legislative thresholds on the minimum number of signatures required to initiate referenda and the time to collect these signatures as strong and exogenous instruments for observed initiatives.
urn:nbn:de:bsz:180-madoc-356150
Keywords: D72; D78; H70; 330; direct democracy; local public finances; Germany